2016
DOI: 10.1007/s11999-016-5037-3
|View full text |Cite
|
Sign up to set email alerts
|

What Factors are Associated With Clinically Important Improvement After Shoulder Hemiarthroplasty for Cuff Tear Arthropathy?

Abstract: Background In selected patients with a desire to maintain activity levels greater than those recommended after reverse total shoulder arthroplasty, hemiarthroplasty remains an option for treatment of cuff tear arthropathy (CTA). However, given the relatively small case series that have been reported to date, little is known regarding which patients will show functional improvement after this surgery.Questions/purposes We asked: What factors are associated with achieving the minimum clinically important differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Roy et al [42] suggested that the minimal clinically important difference for the SST in shoulder arthroplasty is 3. Others have suggested that the minimal clinically important difference is 30% of the MPI from preoperative to latest followup [11,31,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roy et al [42] suggested that the minimal clinically important difference for the SST in shoulder arthroplasty is 3. Others have suggested that the minimal clinically important difference is 30% of the MPI from preoperative to latest followup [11,31,48].…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al [22] reported an extensive validation for the use of the SST in patients having shoulder arthroplasty. From the results of clinic visits and from routinely mailed followup questionnaires documented in a longitudinally maintained database, we recorded the preoperative SST, 2-year postoperative SST, preoperative to postoperative change in SST, percent of maximum possible improvement (%MPI) in the SST calculated as: (followup SST score À preoperative score)*100% / (12 À preoperative score) [11,31,48], and any history of postoperative dislocation or subluxation.…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in functional scores and range of motion were also observed, with a 95% patient satisfaction rate at an average follow-up of 20 months. Somerson et al 38 evaluated a mixed cohort of traditional and CTA hemiarthroplasty prostheses and reported that patients with an intact teres minor, intact subscapularis, and lower preoperative external rotation had a better prognosis for achieving clinical improvement after hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…When applying these MCID thresholds in future studies, researchers should take care that these thresholds are always an average estimate and that individual patients may have greater or lower thresholds for perceiving an important change. Given the risk of ceiling effects in EQ-5D-3L, it might be more appropriate to use a relative measure of improvement, such as the percentage of possible improvement (PPI) following Gilmer et al 47 and Somerson et al 48 in addition to the change score.…”
Section: Comparison With Other Population Value Setsmentioning
confidence: 99%